The use of point-of-care ultrasound in the diagnostic screening of Stanford A aortic dissection associated with stroke - Rosa de Sousa, Giovanna; Junqueira Reis Ferraz, Marta; Izoton, Igor; Lima Machado, Alexandre; Balen Ronsoni, Vinicius; Pedro Pereira, Victor; Brigato de Araújo Sanchez, Ricardo; Januzzi, Werlley (LAJEC - Latin American Journal of Emergency Care, 2024)
Acute aortic dissection is a pathology with high lethality and a wide variation in clinical presentations, which makes diagnosis and early treatment diffi cult. Point-of-care ultrasound, a methodology increasingly present in the emergency department, has proven to be an important ally in the early diagnosis of acute aortic dissection and its complications. This work reports a case of acute aortic dissection with stroke and the assistance of point-of-care ultrasound in this scenario.